Polymeric layer-by-layer films composed by natural polymers and based on the adhesive properties of mussels for biomedical applications - Neto, Ana I. (2013)
Publicado em "Journal of Tissue Engineering and Regenerative Medicine", vol. 7, supp. 1 (2013)